1991
DOI: 10.1128/jb.173.13.4195-4202.1991
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of Escherichia coli type 1 fimbriae exposes cryptic D-mannose-binding sites

Abstract: Cells of the gram-negative bacterium Escherichia coli are able to attach to various host cells by means of a mannose-specific adhesin associated with type 1 fimbriae. Here we show that fragmentation of type 1 fimbriae by freezing and thawing results in increased mannose-binding activity as demonstrated by increased hemagglutination, increased stimulation of human lymphocyte proliferation, and increased binding of the mannose-containing enzyme horseradish peroxidase. Increased activity in all three assays was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 21 publications
3
34
0
Order By: Relevance
“…In addition, in the sfp operon, homologues of papI and papB could not be detected (Brunder et al, 2001). As the pix operon apparently does not contain genes encoding a tip-associated fibrillum, these data might indicate that the actual adhesin might not be located at the tip but instead could be periodically intercalated in the pilus rod (Ponniah et al, 1991).…”
Section: Discussionmentioning
confidence: 87%
“…In addition, in the sfp operon, homologues of papI and papB could not be detected (Brunder et al, 2001). As the pix operon apparently does not contain genes encoding a tip-associated fibrillum, these data might indicate that the actual adhesin might not be located at the tip but instead could be periodically intercalated in the pilus rod (Ponniah et al, 1991).…”
Section: Discussionmentioning
confidence: 87%
“…Thus, the oligomeric complex in the FimDCGH sample may consist primarily of a rod-like structure. It has been suggested previously that occasionally FimH can be intercalated within the type 1 pilus rod (30,34,35); the relative quantities of FimG and FimH in the FimDCGH assembly intermediate (Fig. 2 A, lane 2) suggest that there may be multiple FimH subunits in the multimer that is formed.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesized explanation for this phenomenon was pilus retraction, and another was physical impedance of outward pilus growth by the host cell (3). It has been suggested previously that FimH intercalation would result in relatively weak points in the type 1 pili, which are thought to be prone to breakage (35). Such breakage could also account, in part, for the shortening of pili that has been seen during the early stages of infection (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for this to be true, FimH presented at the fimbrial tip as well as FimH intercalated along the shaft would both have to be able to mediate adhesion. Much previous work has indicated that only FimH present at the tips of fimbriae is functional in mediating adhesion (35,(45)(46)(47)(48). For example, type 1 fimbriae have been observed to bind to erythrocyte membranes as well as the uroepithelium by the tips of the fimbriae (46,49).…”
Section: Discussionmentioning
confidence: 99%